Plant-Produced Receptor-Binding Domain of SARS-CoV-2 Elicits Potent Neutralizing Responses in Mice and Non-human Primates - Siriwattananon, Konlavat; Manopwisedjaroen, Suwimon; Shanmugaraj, Balamurugan; Rattanapisit, Kaewta; Phumiamorn, Supaporn; Sapsutthipas, Sompong; Trisiriwanich, Sakalin; Prompetchara, Eakachai; Ketloy, Chutitorn; Buranapraditkun, Supranee; Wijagkanalan, Wassana; Tharakhet, Kittipan; et al. (Frontiers in Plant Science, 2021)
The emergence of coronavirus disease 2019 (COVID-19) caused by novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected global public health and economy. Despite the substantial efforts, only few vaccines are currently approved and some are in the different stages of clinical trials. As the disease spreads rapidly, an affordable and effective vaccine is urgently needed. In this study, we investigated the immunogenicity of plant-produced receptor-binding domain (RBD) of SARS-CoV-2 in order to use as a subunit vaccine. In this regard, RBD of SARS-CoV-2 was fused with Fc fragment of human IgG1 and transiently expressed in Nicotiana benthamiana. The plant-produced RBD-Fc fusion protein was purified with a protein A affinity column chromatography. Two intramuscular administrations of plant-produced RBD-Fc protein vaccine formulated with alum as an adjuvant have elicited high neutralization titers in immunized mice and cynomolgus monkeys. Further it has induced a mixed Th1/Th2 immune responses and vaccine-specific T-cell response confirmed by interferon-gamma (IFN-γ) enzyme-linked immunospot assay. Altogether, our results suggest that plant-produced SARS-CoV-2 RBD has the potential to be used as an effective vaccine candidate against SARS-CoV-2.